The finance curse: how global finance is making us all poorer - Shaxson, Nicholas (London, 2018)
"Global finance is a system that works for the few and against the many. We need finance – but when finance grows too big it becomes a curse. The City of London is the single biggest drain on our resources; it sucks talent out of every sphere, it siphons wealth and hoovers up government time. Yet to be ‘competitive’, we’re told we must turn a blind eye to money-laundering and appease big business with tax cuts. We are told global finance is about wealth creation; the reality is wealth extraction. Tracing the curse back through economic history, Shaxson uncovers how we got to this point. He exposes offshore tax havens; the uncontrolled growth of monopolies; the myths around the Celtic Tiger and its low corporate tax rate; the bizarre industry of wealth management; the destructive horrors of private equity; and the sinister ‘Competitiveness Agenda’. Nicholas Shaxson revealed the dark heart of tax havens long before the Panama and Paradise Papers. Now he tells the explosive story of how finance established a stranglehold on society and points us towards a way out. "